The school needs a Copernican revolution - Ansión, Juan (1993)
More than once I heard a teacher sincerely concerned about his students say: "The problem is that children do not adapt to school." This is a lucid finding but at the same time reveals a very marked bias in the perception that the teacher has of the student and of the role of the school. Lucid verification in effect: the teacher thus observes a marked distance between the social and cultural world of the student and that of the school, this distance is what makes it difficult for the child to adapt to the school environment. But verification at the same time formulated unilaterally, since it supposes that, given the existing distance, the child is the one who must adapt, change to adapt the school.